PENGENDALIAN KUALITAS PELAYANAN PADA NABILA LAUNDRY SYAR'I - Situmorang, Lilis; Sumantika, Arsyad (LPPM Universitas Putera Batam, 2023)
Nabila Laundry-Syar'i is one of the SMEs in the service sector that is currently developing in Tanjung Piayu Village, Sei Beduk District, Batam City, to be precise in the Pancur Baru Block L No. 10. Nabila Laundry Syar'i still often gets complaints from customers. Some of the things that become customer complaints are the exchange of clothes between customers, damage to customer clothes, loss of customer clothes, clothes taking time that is longer than the specified time. This study uses the Service Quality method, namely Tangible, Reliability, Responsiveness, Assurance Empathy with the highest gap value in the Reliability dimension with the attribute of suitability of clothes when delivered and sent home with a gap of -0.517 and uses the CSI method to determine the level of customer satisfaction with a value The CSI obtained was 79.365% and the index value number four which showed an index value of 66.00 – 80.99 gave agreed results, which stated that customers agreed with the performance of the services that Nabila Laundry Syar'i had provided, but some were still not optimal overall. Nabila Laundry Syar'i is committed to improving the poor service work system to create more satisfaction in the future.